The Influence of Physical Fitness, Motor Skills, and Learning Motivation on Cartwheel Skills in Physical Education - Hamda Putra Darma; Bafirman Bafirman; Sayuti Syahara; Khairuddin Khairuddin; Dally Rahman; Fiky Zarya (Jurnal Penelitian Pendidikan IPA, 2024)
Background Problems: During the observation, many students were unable to perform cartwheel skills. This research is important so that students can pass the minimum completion criteria so that their physical education learning outcomes are not low. Research Objectives: This study aims to determine the factors that influence the skills of cartwheel. Methods: This type of research is quantitative. The population amounted to 392 students in class XI. The technique used to obtain the sample is simple random sampling using the slovin formula with an error rate of 10%. Based on this, the sample amounted to 80 students. The physical fitness test instrument used the Indonesian Student Fitness Test, the motor ability test instrument used the Barrow Motor Ability Test, the learning motivation data was collected using a questionnaire, and the cartwheel skill data used an observation sheet which contained the criteria for implementing the cartwheel movement. Path analysis was used as a data analysis technique. Finding/Results: The results of the study consist of: 1. Physical fitness and motor skills have a significant influence on cartwheel skills. 2. Learning motivation has no significant effect directly on cartwheel skills. 3. Physical fitness indirectly through learning motivation has no significant effect on cartwheel skills. 4. Motor ability indirectly through learning motivation has no significant effect on cartwheel skills. Conclusion: Physical fitness and motor skills have a significant influence on cartwheel skills. Students need to do it outside of PJOK class hours. For Further Researchers Conduct research on other gymnastic movements.